Penggunaan Media Sosial Dan Kualitas Tidur Pada Remaja - Ari Athiutama; Ridwan Ridwan; Indra Febriani; Imelda Erman; Aldella Trulianty (Poltekkes Kemenkes Bengkulu, 2023)
Social media allows everyone to interact and share various activities in the form of photos or videos. Most social media users are teenagers. Social media is a need that can become addictive for teenagers. Excessive use of social media can have a negative impact on adolescents such as the poor quality of adolescent sleep. The purpose of this study was to analyze the relationship between social media use and sleep quality in adolescents. This research was conducted quantitatively using a cross-sectional design with a sampling technique that is accidental sampling and obtained a total sample of 91 respondents, namely adolescents and data collection using a questionnaire on the intensity scale of social media use (SIPMS) and the Pittsburgh Sleep Quality Index (PSQI). The results of the Chi Square test, obtained a p value = 0.025, which means that most teenagers who use active social media have poor sleep quality. Active use of social media can disrupt sleep patterns more when compared to passive use of social media, so researchers hope that there will be treatment that can be done to manage time and patterns of social use so that the sleep quality of social media users is good, especially in adolescents.